Cancer Therapy: Multifunctional Carbon–Silica Nanocapsules with Gold Core for Synergistic Photothermal and Chemo‐Cancer Therapy under the Guidance of Bimodal Imaging (Adv. Funct. Mater. 24/2016). (June 2016) - Li, Linlin; Chen, Chuanfang; Liu, Huiyu; Fu, Changhui; Tan, Longfei; Wang, Shunhao; Fu, Shiyan; Liu, Xi; Meng, Xianwei; Liu, Hong
Abstract : On page 4252, L. L. Li, H. Y. Liu, H. Liu, and co‐workers demonstrate a multi‐functional nanoplatform for cancer theranostics, based on carbon–silica nanoparticles with a gold nanoparticle core. Doxorubicin can be encapsulated and released in a controlled manner using pH and near‐infrared light stimuli, leading to spatiotemporal targeting to reduce off‐target toxicity.